Oral and dental aspects of child abuse - Arlette Suzy Puspa Pertiwi; Inne Suherna Sasmita (Dental Journal (Majalah Kedokteran Gigi), 2006)
Child abuse is defined as those acts or omissions of care that deprive a child from the opportunity to fully develop his or her unique potentials as a person either physically, socially or emotionally. The overall incidence of child abuse is not really clear. Statistical data do not show the actual rate because of the unreported cases. Dentists are in a strategic position to recognize and report the children being abused because they often see the child and parents interacting during multiple visits and over a long period of time. The orofacial region is commonly traumatized during episodes of child abuse. The characteristics and diagnostic finding of child abuse, and the protocol of reporting such cases, should be familiar to the dentist so that appropriate notification, treatment and prevention of further injury can be instituted. Dentists with experience or expertise in child abuse and neglect will strengthen their ability to prevent and detect child abuse and neglect and enhance the ability to care for and protect children. This paper discusses the oral and dental aspects of child abuse and the dentist role in evaluating this situation including prevention of child abuse.